The DNA Data Storage Model - Landsman, Dave; Strauss, Karin (IEEE Computer, 2023)
Reliably storing digital data in synthetic DNA fits naturally into the layered Open Systems Interconnect model and shares many parallels with reliably storing data using existing storage technologies and interfaces. DNA data storage, or using synthetic DNA as a data storage medium, is being seriously considered as an archival storage solution due to its volumetric data density potential, data retention characteristics, sustainability, and potential for dramatically lower total cost of ownership versus existing storage technologies.